Letter from the Editor (International Journal of First Aid Education)
This letter introduces the articles of the issue, contextualizing the work in the wake of the 2021 United Nations Climate Change Conference (COP26) and arguing for a similar approach to addressing climate change in first aid as the previous issue (Vol. 4, No. 1) made to addressing COVID-19, raising the question, "So how can we raise our voice on the role of first aid education as a public health solution, which is apolitical and evidence-based?"